2020
DOI: 10.1186/s40478-020-00972-z
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed balance in the expression of MMP9 and TIMP3 in cerebral amyloid angiopathy-related intracerebral haemorrhage

Abstract: Cerebral amyloid angiopathy (CAA) is characterized by the deposition of the amyloid β (Aβ) protein in the cerebral vasculature and poses a major risk factor for the development of intracerebral haemorrhages (ICH). However, only a minority of patients with CAA develops ICH (CAA-ICH), and to date it is unclear which mechanisms determine why some patients with CAA are more susceptible to haemorrhage than others. We hypothesized that an imbalance between matrix metalloproteinases (MMPs) and their inhibitors (TIMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Remarkably, we identified two proteins selectively associated with cerebrovascular Aβ, TIMP3 and MFG-E8. We focused our study on the MFG-E8 candidate since TIMP3 has been previously described in vessels from CAA patients [ 15 , 44 ]. Our proteomic results demonstrated that the LCM approach using an experimental transgenic model was a reliable tool that successfully validated candidates previously identified in other studies on humans.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, we identified two proteins selectively associated with cerebrovascular Aβ, TIMP3 and MFG-E8. We focused our study on the MFG-E8 candidate since TIMP3 has been previously described in vessels from CAA patients [ 15 , 44 ]. Our proteomic results demonstrated that the LCM approach using an experimental transgenic model was a reliable tool that successfully validated candidates previously identified in other studies on humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tissue endogenous inhibitors (TIMPs) and matrix metalloproteinases (MMPs) are involved in regulation of the ECM, and dysregulation of these proteases can result in decreased turnover of ECM components and/or damage the integrity of the BBB, contributing to lobar hemorrhage. 65,77,78 MMP2 and MMP9 are enhanced in CAA with AD pathology, and matrix metalloproteinase inhibitor TIMP3 is enhanced in CAA both with and without underlying AD pathology. 40,70,78,79 MMP2 and MMP9 have also been shown to proteolyze various Ab peptides in AD.…”
Section: Protein Accumulation and Signaling Dysregulation In Caamentioning
confidence: 96%
“…Upon ischemic stroke, MMP-9 is secreted by the cells forming the neurovascular unit via regulation of the extracellular signal-regulated kinase-(ERK)-1/2) and the signal transducer and activator of transcription (STAT)-3 pathways, leading to the degradation of basal lamina/extracellular matrix (ECM) proteins, and the recruitment and extravasation of peripheral immune cells (Nishikawa et al, 2018;Jäkel et al, 2020). Interestingly, human brain studies showed that MMP-9 is implicated in the degradation of type IV collagen at the basal lamina, resulting in hemorrhagic transformations (Rosell et al, 2006(Rosell et al, , 2008, enhanced leukocyte infiltration, and poor neurological outcomes (Kim et al, 2016).…”
Section: Bbb Dysfunctionmentioning
confidence: 99%